1992
DOI: 10.1002/j.1460-2075.1992.tb05096.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA binding by c-Ets-1, but not v-Ets, is repressed by an intramolecular mechanism.

Abstract: The E26 avian retrovirus causes an acute leukemia in chickens and transforms both myeloid and erythroid cells. The virus encodes a 135 kDa fusion protein which contains amino acid sequences derived from the viral Gag protein and the two cellular transcription factors c‐Myb and c‐Ets‐1p68. Previously we have shown that like v‐myb, v‐ets on its own is also active in transformation, but only within the erythroid lineage. To understand better the mechanisms involved in the oncogenic activation of c‐Ets‐1p68, we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 39 publications
(37 reference statements)
6
113
1
Order By: Relevance
“…Human ETS-1, p54 (ETS-1, hereafter) binds DNA through domain E, the highly conserved ETS domain. The neighboring domains D and F a ect the a nity and selectivity of DNA binding by forming a`closed' structure (Hagman and Grosschedl, 1992;Lim et al, 1992;Hahn and Wasylyk, 1994;Fisher et al, 1994;Peterson et al, 1995). Domain B, also called the`Pointed' domain, is conserved among several Ets members.…”
Section: Isolation Of Huubc9 With a Yeast Two-hybrid Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Human ETS-1, p54 (ETS-1, hereafter) binds DNA through domain E, the highly conserved ETS domain. The neighboring domains D and F a ect the a nity and selectivity of DNA binding by forming a`closed' structure (Hagman and Grosschedl, 1992;Lim et al, 1992;Hahn and Wasylyk, 1994;Fisher et al, 1994;Peterson et al, 1995). Domain B, also called the`Pointed' domain, is conserved among several Ets members.…”
Section: Isolation Of Huubc9 With a Yeast Two-hybrid Systemmentioning
confidence: 99%
“…This might re¯ect the importance of intra-molecular regulation of ETS-1 activity. The DNA binding activity of the ETS domain is inhibited by the surrounding domains D and F, which form a`compact',`closed' structure (Hagman and Grosschedl, 1992;Lim et al, 1992;Hahn and Wasylyk, 1994;Fisher et al, 1994;Peterson et al, 1995). Similarly, there are functional interactions between the B and C domains, that are consistent with intra-molecular regulation (Schneikert et al, 1992).…”
Section: The Transcriptional Activity Of Ets-1 Is Increased In the Prmentioning
confidence: 99%
“…This suggested that autoinhibition was an independent phenomenon from the selection of specific DNA sequences. We therefore tested a variant in which the C-terminal fragment of the protein had been removed while keeping the exon VII-coded region intact (DC415 in Figure 7), thus creating a mutation known to release the autoinhibition state of Ets-1 (Lim et al, 1992;Jonsen et al, 1996). This DC415 variant displays similar differences than p51Ets-1 in binding to the Opt and Opt[C À1 G] DNA probes, confirming that autoinhibition and specific DNA sequence recognition are separate properties of Ets-1.…”
Section: Quantification Of P51ets-1 and P42ets-1 Binding To Dnamentioning
confidence: 99%
“…EWS/FLI-1 differs from FLI-1 at its amino-terminal domain. The amino-terminal sequences of some Ets proteins can modulate the avidity of DNA binding (12,28). Alternatively, EWS/FLI-1 and FLI-1 may bind target sites with similar affinities, but EWS/FLI-1 may be a more potent transcriptional activator.…”
Section: Ews/fli-1 Transforms Nih 3t3 Cells But Fli-1 Does Notmentioning
confidence: 99%